Air Starvation Induced Degradation in Polymer Electrolyte Fuel Cells. Issue 1 (2nd February 2017) - Bodner, M.; Schenk, A.; Salaberger, D.; Rami, M.; Hochenauer, C.; Hacker, V.
Abstract: While hydrogen starvation in fuel cells is intensely investigated and strategies for avoidance have been developed, almost no data are available for other unexpected events, such as malfunction of the air supply. In this study we induce oxygen starvation in a manner closer to failure in real systems than commonly applied accelerated stress tests. By cycling the cathode gas flow, two accelerated stress tests were introduced; simulating short periods of air starvation with duration of either 10 or 60 seconds. Short cathode undersupply does not lead to fuel cell failure. Air starvation results in a voltage drop and hydrogen evolution. This is accompanied by the reduction of platinum oxides in the respective areas, which leads to an improvement of the active catalyst surface area. After extensive cycling, degradation becomes the dominant effect. X‐ray computed tomography is used to visualize the change of the catalyst particle size and distribution in dependence on the location in the fuel cell. Throughout the experiments, a total voltage decay rate of 1.427 mV h −1, a total fluoride emission rate of 0.0031 µmol h −1 cm −2 and severe current and temperature gradients during starvation were observed, leading to an inhomogeneous agglomeration of the platinum electrocatalyst.